Psychosocial risks and mental health of preschool care providers in Kuala Lumpur, Malaysia: a cross-sectional study - Sin Wan Tham; Min Fui Wong; Maslinor Binti Ismail; Noriklil Bukhary Binti Ismail Bukhary (BMC Psychology)
Abstract Background Child maltreatment in daycare is a public health issue. As childcare is stressful, high care provider negativity independently predicts more internalizing behaviour problems, affecting children’s psycho-neurological development. This study aimed to determine psychosocial factors associated with the mental health of preschool care providers in Kuala Lumpur. Methods A random cluster sampling cross-sectional survey was conducted in 2019. The study involved registered care providers for preschoolers under four years old without acute psychiatric illness. The Center for Epidemiologic Studies Depression Scale (Malay-CES-D) and Karasek’s Job Content Questionnaires (Malay-JCQ) were used to assess depression symptoms and psychosocial job-related risks. Logistic regression (p < 0.05) guided by the Hosmer-Lemeshow strategy was used for analysis, with the final model evaluated for assumptions and goodness-of-fit. Results A total of 247 providers were recruited from 36 preschools. All respondents were females, with a mean age of 32.1 years old, Malays (70.4%), married (55.0%), attained a diploma and above (50.6%) and had low income (80.1%). The prevalence of depressive symptoms and job strain was 28.7%. Final logistic regression revealed individual factors (married, stressful life events: assault and marital issues), job strain (AOR = 2.33, CI = 1.22, 4.44), and job insecurity (AOR = 1.29, CI = 1.07, 1.56) determine depressive symptoms. Good supervisor support was inversely associated with depression. Conclusions Job strain and insecurity contribute significantly to depressive symptoms among preschool care providers in Kuala Lumpur. The Social and Welfare Department can promote supportive supervision through skill training for supervisors, fostering a positive mental health environment for improving workers’ mental health.